Externalist internalism: essays on hybrid theories in the philosophy of mind and epistemology - Bartholain, M (2023)
This thesis collects four chapters connected by the theme of hybridity across theories in the philosophy of mind and epistemology. More precisely, this thesis assesses the consistency of hybrid epistemic internalism, a view that combines externalism about mental states with epistemic internalism.